Servqual Influence on Customer Satisfaction, Complaints, Engagement, and Loyalty in Indonesia’s Biggest Internet Provider - Malinda Puteri Kusaeni; Sri Rahayu Hijrah Hati (Syntax Literate, 2022)
Since the epidemic, digitization has advanced more quickly than anybody could have anticipated. From 2019 to 2021, IndiHome's product surpasses its rivals by controlling more than 80% of the market share. On the other hand, it is paradoxical that IndiHome would lose close to 10% of its customers in 2022 while also gaining more. This study aims to examine the influence of service quality and lead to customer satisfaction on IndiHome by PT. Telkom Indonesia. In addition, the researcher also explores the relationship between customer satisfaction, customer complaints, customer engagement, and customer loyalty in the telecommunication industry. With information gathered from users in the Jabodetabek area, SEM PLS will be utilized to examine the association between the dependent and independent variables individually. Results indicated that CS is crucial, particularly for internet service providers where SQ is important. The results also found that customer satisfaction and customer engagement have a positive effect on customer loyalty. But the relationship of customer satisfaction toward customer complaints, then toward loyalty, is shown to be unsignificant. The findings give marketers in the same business a scientifically validated example from Indonesia's largest internet service provider to sharpen competitiveness in the industry's constantly expanding market. This research was conducted only focused on revealing the relationship between customer satisfaction and customer complaints then to loyalty, without analyzing what factors lead to customers filing a complaint. Therefore, future research is expected to be able to test the determinant factors of the complaints.